Martuccelli, Danilo. Lima and its arenas. Social powers and cultural hierarchies. Lima: Causces Editores, 2015, 326 pp. - Mitrovic Pease, Alejandro Mijail (2016)
Danilo Martuccelli proposes a reading of the processes that make up the individual and collective experience in contemporary Lima. The author argues that sociability in Lima is articulated through an informal matrix that structures the city as multiple arenas of conflict that determine the viability of a new citizen project.